An Efficient Approach For Dynamic Stability Analysis of Power Systems - Including Load Effects - El-Din, Magdy Zein Hussain (My University, 1977)
This thesis describes an efficient approach for modeling and analysing small signal (dynamic) stability of balanced interconnected power systems. Systems are modeled into the state-space form where a partitioning technique is used to systematically reduce system equations into that form. Consequently, eigenvalue and eigenvalue sensitivity methods are used for dynamic stability prediction.
The formulation technique allows the inclusion of nonlinear and dynamic load representation and network and shaft dynamics in addition to detailed generator, turbine-governor and excitation system simulations currently being used by industry. The partitioning approach eliminates the need for storing large blocks of null elements. It also preserves the identity of various sub-systems. Consequently, this approach is particularly economical in studies involving system modification updating.
An algorithm is developed to calculate eigenvalue second-order sensitivities with respect to system control and design parameters. The sensitivities are obtained in terms of the eigenvalues and eigenvectors of the base case coefficient matrix. It is shown that the inclusion of the second-order terms in an overall sensitivity package does not add any computational complexity.
Eigenvalue first and second-order sensitivities are combined with an inverse iteration technique in an efficient algorithm for tracking possible movement of any sensitive subset of system eigenvalues due to parameter changes. The method is applicable in situations where a relatively small number of eigenvalues are critical in describing system dynamic stability. The efficiency of this algorithm over the repeated eigenvalue method is demonstrated.
These concepts and techniques are applied to a number of practical problems currently receiving attention in the power industry. In particular situations involving insufficient damping torque due to interaction between turbine-generator and network dynamics, turbine-generator and stabilization control, and the effect of static excitation and induction motor loads are analysed.
The interactions between system composite loads and excitation-stabilization control loops are examined on a reasonably general basis. It is shown that load characteristics have a considerable effect on system stability. It is also shown that there are specific situations where the choice of the load model can make a difference in stability prediction. In particular, at light generation levels the use of a power system stabilizer with a constant power local load leads to a prediction of instability while stability is predicted for a constant impedance load model.
Keywords: Electrical and Electronics; Electrical and Electronics